AGING-ASSOCIATED LOSS OF ARNT SIGNALING IMPAIRS SKELETAL MUSCLE REGENERATION. (16th November 2018) - Li, B; Sinha, I; Sakthivel, D; Udeh, K; Panayi, A; Kah Yong, T; Bhasin, S; Wagers, A
Abstract: Purpose: Skeletal muscle regeneration is required for the maintenance of muscle mass in aging. Hypoxia signaling, including aryl hydrocarbon nuclear translocator (ARNT), is necessary to maintain regenerative potential. The present study evaluates whether loss of hypoxia signaling in aging directly limits skeletal muscle precursor (SMP) regenerative potential. Methods: Young (Y, 8–12 weeks) and old (O, 21–23 months) mice were utilized to determine changes in regenerative potential and skeletal muscle hypoxia signaling that occur with aging. Whole muscle was utilized for immunoblotting, PCR, and fluorescence activated cell sorting for SMP isolation. HSA-Cre ER ARNTfl/fl mice were used to create mice with muscle specific loss of ARNT following activation. Results: SMP frequency and myogenic potential decrease dramatically in aging (p<0.001). Cross-sectional area in regenerating fibers decreases by 40% in O mice as compared to Y following injury (p<0.01). In whole, hind-limb skeletal muscle, we found that ARNT levels are 4.7-fold lower by PCR (p<0.01) and 5-fold lower by immunoblotting in O versus Y mice (p<0.01). Young, tamoxifen-activated HSA-Cre ER ARNTfl/fl mice, created to mimic the loss of hypoxia signaling in old mice, exhibit an 80%, skeletal muscle specific decrease in ARNT and VEGF expression and protein levels following injury (p<0.01) and a 25% decrease in skeletal muscle fiber cross sectional area (p<0.01) as compared to littermate controls. Conclusion: Hypoxia signaling declines with aging and contributes to loss of skeletal muscle regeneration. Restoring the hypoxia pathway may promote regeneration and prevent muscle loss in aging.